The perforated uterus. (16th October 2013) - Shakir, Fevzi; Diab, Yasser
<x xml:space="preserve">Abstract</x> Key content Uterine perforation is an uncommon but potentially serious complication of uterine manipulation, evacuation of retained products of conception or termination of pregnancy (TOP), hysteroscopic procedures and during coil insertion. Factors that increase the risk of uterine perforation include uterine anomalies, infection, recent pregnancy and postmenopause. TOP is the most common procedure associated with uterine perforation. Prevention of uterine perforation is favoured, although if it occurs, initial recognition together with immediate and ongoing management is key to reducing morbidity, mortality and long‐term consequences. It is important that surgeons performing surgical TOP are adequately trained. The experience of the surgeon results not only in fewer perforations but also in the early recognition of uterine injury. Uterine perforation is a complication that is well recognised by all gynaecologists, although subsequent assessment and management needs to be standardised. Learning objectives To be aware of the incidence of uterine perforation and the potential serious complications that can result. To identify the risk factors of uterine perforation, the mechanism of injury and how to potentially prevent it from occurring. To increase awareness of this complication and to propose a standardised management protocol if a uterine perforation occurs, together with risk management issues. Ethical issues Are women at increased risk of uterine perforation counselled adequately about the complications and consequences? Are women at increased risk given the full range of alternative treatment options?